Relationships between Lateral Limb Bias, Turnout, and Lower Limb Injury in a Female Pre-Professional Ballet Dancer Population. Issue 2 (June 2021) - McMahon, Elise; Pope, Rod; Freire, Kate
Dancers are known to have specific limb preferences when they dance and commonly experience lower limb injury, especially early in their training. The primary aim of this study was to determine and examine the relationships between lateral limb bias, perceived turnout profile, and lower limb injury history in female pre-professional ballet dancers using current definitions of lateral bias, leg dominance, and the concept of "working" and "supporting" legs in dance. A cross-sectional survey design with retrospective recall of 12-month injury history was employed. An online questionnaire was distributed to female dancers between the ages of 16 and 21 years who were training in classical ballet at the pre-professional level in Australia. The questionnaire gathered information regarding laterality, perceived turnout asymmetry, and self-reported 12-month injury profile. Descriptive and correlation analyses were employed to describe dancer profiles and determine relationships between the three variables. Thirty-two dancers participated. The majority of participants (67%) had right-side dominance and most indicated the right leg as their preferred supporting leg (86.7%) and working leg (60%). A total of 17 participants (53.1%) reported at least one injury in the preceding 12-month period and the side injured was significantly correlated with leg dominance (rs = 0.595, p = 0.012), with the majority of injuries also affecting the preferred supporting and working leg. Dancer perceptions regarding turnout range were correlated with their perceptions of leg dominance (rs = 0.556, p = 0.001), but no statistically significant associations were found between perceptions of turnout range and injury side. In pre-professional dancers, the dominant and the preferred supporting or working leg tend to be the same leg, and the results suggest that the dominant and preferred supporting and working leg of dancers are at greatest risk of injury.